Artificial Intelligence Integration in UNCLOS Implementation for Resolving Maritime Disputes in South China Sea - Al Hafiz, Si Yusuf; Al Badi’ah, Nurul Izzah; Abdurrozaq, M. (Hakamain: Journal of Sharia and Law Studies, 2025)
This research investigates the integration of Artificial Intelligence (AI) into the implementation of the United Nations Convention on the Law of the Sea (UNCLOS) to enhance the effectiveness of maritime dispute resolution, particularly in the South China Sea—a region marked by overlapping territorial claims and geopolitical tensions. The objective of this study is to explore how AI technologies can support legal mechanisms under UNCLOS in resolving disputes more efficiently, transparently, and equitably. Using a normative legal research method with a conceptual and statutory approach, this study examines existing legal frameworks, analyzes the potential of AI-based tools such as machine learning, big data analytics, and automated decision-making systems, and evaluates their relevance in UNCLOS enforcement and dispute resolution mechanisms. The findings indicate that AI can play a transformative role in various aspects: real-time maritime monitoring, evidence verification, predictive modeling of potential conflicts, and assisting international tribunals in the interpretation and application of UNCLOS provisions. Furthermore, AI can facilitate trust-building among stakeholders by ensuring transparent data processing and minimizing human bias. The study concludes that while the integration of AI into UNCLOS implementation poses regulatory, ethical, and technical challenges, it also presents a timely and innovative opportunity to modernize international maritime governance. As an academic contribution, this research offers a forward-looking framework for the digital transformation of international legal instruments and encourages interdisciplinary dialogue between law, technology, and policy in addressing complex maritime disputes such as those in the South China Sea. Keywords: UNCLOS 1982, international maritime law, maritime governance, dispute resolution, maritime law reform.